Comparison of SAW and Topsis Methods in The Selection of The Best Online Bike Shops - Pri Camelia Marissa Jannah; Rani Irma Handayani; F. Lia Dwi Cahyani (LPPM Universitas Bina Sarana Informatika, 2023)
The need for information technology in this pandemic era is greatly increasing. Many people meet their needs by doing buying and selling transactions as if they were online. Through a decision support system using the SAW (Simple Additive Weighting) and TOPSIS (Technique for Others Reference by Similarity to Ideal Solution), methods can provide the best decision in choosing the best online bicycle store site. On the result of the calculation, it is obtained that the results of the two are appropriate. The SAW and TOPSIS methods produced the same ranking, namely the Rodalink site got the highest ranking with a value of 1.019 on the SAW method of 0.833 on the TOPSIS method followed by serbasepeda, united, and cycles. The results of comparing calculations using these 2 methods are considered the SAW method is the most relevant method.